Somatosensory processing in a German family with PINK1 mutations: its potential role in Parkinson disease. Issue 5 (16th April 2009) - Gierthmühlen, J; Lienau, F; Maag, R; Hagenah, J M; Deuschl, G; Fritzer, E; Klein, C; Baron, R; Helmchen, C
Abstract : Background: It is unclear whether sensory symptoms in Parkinson disease (PD) are of primary or of secondary origin attributable to motor symptoms such as rigidity and bradykinesia. Objective: The aim of this study was to elucidate whether sensory abnormalities are present and may precede motor symptoms in familial parkinsonism by characterizing sensory function in symptomatic and asymptomatic PINK1 mutation carriers. Methods: Fourteen family members with PINK1 mutation and 14 healthy controls were examined clinically, with nerve conduction studies and quantitative sensory testing (QST). Results: Thresholds for mechanical detection, mechanical pain and pressure pain were higher in PINK1 mutation carriers compared to controls. Higher thresholds for mechanical detection, mechanical pain and pressure pain were even found in asymptomatic, clinically not or only mildly affected PINK1 mutation carriers. Conclusions: Data suggest that PINK1 -associated PD is associated with a primary hypofunction of nociceptive and non-nociceptive afferent systems that can already be found at the time when motor signs of PD are only subtle. As nerve conduction studies did not reveal differences between PINK1 mutation carriers and controls, we propose that the somatosensory impairment is related to abnormal central somatosensory processing.